Engineered biomaterial delivery strategies are used to reduce cardiotoxicity in osteosarcoma - Hou, Yulin; Wang, Jie; Wang, Jianping (Frontiers in Pharmacology, 2023)
Osteosarcoma (OS) is the most common malignant bone tumor in children and adolescents. Chemotherapy drugs play an integral role in OS treatment. Preoperative neoadjuvant chemotherapy and postoperative conventional adjuvant chemotherapy improve survival in patients with OS. However, the toxic side effects of chemotherapy drugs are unavoidable. Cardiotoxicity is one of the common side effects of chemotherapy drugs that cannot be ignored. Chemotherapy drugs affect the destruction of mitochondrial autophagy and mitochondria-associated proteins to cause a decrease in cardiac ejection fraction and cardiomyocyte necrosis, which in turn causes heart failure and irreversible cardiomyopathy. Biomaterials play an important role in nanomedicine. Biomaterials act as carriers to deliver chemotherapy drugs precisely around tumor cells and continuously release carriers around the tumor. It not only promotes anti-tumor effects but also reduces the cardiotoxicity of chemotherapy drugs. In this paper, we first introduce the mechanism by which chemotherapy drugs commonly used in OS cause cardiotoxicity. Subsequently, we introduce biomaterials for reducing cardiotoxicity in OS chemotherapy. Finally, we prospect biomaterial delivery strategies to reduce cardiotoxicity in OS.